OsNAC15 regulates tolerance to zinc deficiency and cadmium by binding to OsZIP7 and OsZIP10 in rice - Zhan, Junhui; Zou, Wenli; Li, Shuangyuyan; Tang, Jichun; Lu, Xiang; Meng, Lijun; Ye, Guoyou (MDPI, 2022)
Zinc (Zn) deficiency and cadmium (Cd) stress are severe threats to the growth and development of plants. Increasing Zn content and/or decreasing Cd content in grain are also important objectives of rice breeding. However, the molecular mechanisms of Zn deficiency tolerance (ZDT) and Cd stress tolerance (CDT) are largely unknown in rice. Here, we report that a NAM/CUC2-like transcription factor, OsNAC15, contributes to ZDT and CDT in rice. Knockout of OsNAC15 reduced ZDT and CDT at the vegetative stage. OsNAC15 expresses in all tissues of different developmental stages, and is repressed by Zn deficiency and induced by Cd stress. OsNAC15 is a functional transcription factor with transactivation and DNA binding activities. Expression analysis of rice ZIP family genes suggested that the knockout of OsNAC15 activates or inhibits their transcriptions under Zn deficiency or Cd stress conditions. The yeast one-hybrid assay, transient transcriptional activity assay using the dual-luciferase reporter system and electrophoretic mobility shift assay demonstrated that OsNAC15 directly binds to the zinc deficiency-responsive element motifs in the promoters of OsZIP7 and OsZIP10 to repress their transcriptions. The OsNAC15–OsZIP7/10 module is an essential foundation for further study on the regulatory mechanisms of ZDT and CDT in rice.